Loop Excision for Precancers of the Uterine Cervix: Local or General Anaesthetic? - Freisleben, Moritz; Petzel, Anja; Jülicher, Anne; Jonas, Anna; Betzler, Janina; Choly, Natalia; Pashayeva, Esmira; Porthun, Jan; Welcker, Thomas; Schneider, Viola; Kaufmann, Andreas M.; Schneider, Achim (Geburtshilfe und Frauenheilkunde, 2023)
In Germany, treatment of HSIL or AIS of the uterine cervix by loop excision is performed almost exclusively under general anaesthesia (GA). International studies and guidelines show high acceptance of local anaesthesia (LA) due to hermeneutic, medical, and economic factors. We performed an observational comparative study aiming to prove advantages of local anaesthesia within the German health system.In a prospective observational study, patients diagnosed with HSIL or AIS of the uterine cervix were treated at the Institute for Cytology and Dysplasia, Berlin, by loop excision in 2021. We started with a feasibility study: 303 patients diagnosed with HSIL/AIS of the uterine cervix and her colposcopist answered an electronic questionnaire with respect to loop excision under LA.Since we found a high acceptance for LA in patients and colposcopists, we initiated a comparative study LA vs. GA: 322 patients underwent loop excision and selected their mode of anaesthesia: n = 206 LA vs. n = 116 GA. 114 patients of the feasibility study had to undergo loop excision and became part of the comparative study (n = 79 for the LA group, n = 35 for the GA group). All patients received a standardised questionnaire to document their pain score within 24 h after treatment on a visual analogue scale, i.e. VAS, between 0 and 100. 178 patients of the LA group and 80 patients of the GA group completed and returned the questionnaire and form the cohort for our comparison of LA vs. GA. With 191 of these 258 patients, i.e. 74%, a telephone survey was performed to ask for patient satisfaction and the rates of recurrence after a mean interval of 1 year post surgery. We postulate that there will be no clinically relevant significant difference in satisfaction and postoperative pain between patients in the LA group and the GA group.In the feasibility study, 90% (272 of 303) of patients diagnosed with HSIL or AIS were considered eligible for LA by their colposcopists. 75% (227 of 303) of patients were open to loop excision under LA.In the comparative study, 63 of 206 women of the LA group were interviewed preoperatively: 89% would accept a pain score above 20 during the procedure, 33% a pain score above 50 and 11% of max. 20. Postoperatively, the median VAS pain score for loop excision under local anaesthesia was 13.1 in 178 patients, and pain during injection of local anaesthesia was 20.9 (p < 0.001). The VAS pain score 20 minutes post surgery did not differ significantly between 178 patients after local anaesthesia versus 80 patients after general anaesthesia (p = 0.09). The surgeons estimated the patient’s pain significantly less than the patients themselves with an underestimate of −14.63 points on the VAS (p < 0.001).Within 7 days following loop excision under LA, 95.5% of 178 patients would choose local anaesthesia as their preferred method for a potential repeat loop excision, 8.8% of which would like additional painkillers, and 4.5% would choose general anaesthesia.In a telephone follow-up survey of 133 women from the LA group after a mean of 12 months post surgery, 97% were “satisfied” or “very satisfied” with the treatment carried out. For patient satisfaction and postoperative pain, no clinically relevant significant difference was seen between the LA and the GA group.The rate of secondary bleeding (6.7% vs. 8.1%, p = 0.72), recurrence of HSIL/AIS (3.6% vs. 5.2%, p = 0.62), and the distribution of the histopathological R status (R0 89.5% vs. 81.1%, p = 0.73; R1 5.3% vs.12.2%, p = 0.57, Rx 4.1% vs. 5.4%, p = 0.65) showed no significant difference when comparing the LA group versus the GA group.Following loop excision under local anaesthesia, more than 95% of patients would choose this method again for repeat surgery. One year post surgery, 97% of the patients were “satisfied” or “very satisfied” with the treatment under local anaesthesia. Offering local anaesthesia for loop excision to patients should be mandatory and included in current guidelines.Schlingenexzisionen zur Therapie von HSIL oder AIS der Cervix uteri werden in Deutschland fast ausschließlich in Allgemeinnarkose (AA) durchgeführt. Internationale Studien und Leitlinien zeigen eine Präferenz für Lokalanästhesie (LA) aus hermeneutischen, medizinischen und ökonomischen Gründen. Mit dem Ziel, die Alternative der örtlichen Betäubung auch den Frauen im deutschen Gesundheitssystem zukommen zu lassen, führten wir eine vergleichende Beobachtungsstudie durch.In einer prospektiven Beobachtungsstudie wurden Patientinnen mit der Diagnose HSIL oder AIS der Cervix uteri im Institut für Zytologie und Dysplasie, Berlin, mittels Schlingenexzision im Jahre 2021 behandelt. Zunächst wurden in einer Machbarkeitsstudie 303 Patientinnen mit der Diagnose einer HSIL/AIS der Cervix uteri und ihr/ihre Kolposkopiker*in mittels eines elektronischen Fragebogens zur Option Schlingenexzision in LA befragt.Da diese Befragung eine hohe Akzeptanz für LA bei Patientinnen und Kolposkopiker*innen ergab, initiierten wir eine Vergleichsstudie von LA vs. AA: 322 Patientinnen wurden mittels Schlingenexzision behandelt und wählten selbst das Anästhesieverfahren: n = 206 in LA vs. n = 116 in AA. Aus der Machbarkeitsstudie hatten 114 Patientinnen die Indikation zur Schlingenexzision und wurden Teil der Vergleichsstudie (n = 79 für die LA-Gruppe, n = 35 für die AA-Gruppe). Allen Patientinnen wurde ein standardisierter Fragebogen mitgegeben, mit dem der Schmerzscore bei einer visuellen Analogskala (VAS) zwischen 0 und 100 innerhalb von 24 Stunden postoperativ erfasst wurde. 178 Frauen der LA-Gruppe und 80 Frauen der AA-Gruppe beantworteten den postoperativ mitgegebenen Fragebogen und bilden somit die Kohorte für unsere vergleichende Untersuchung. 191 dieser 258 Patientinnen, i. e. 74%, konnten nach einer mittleren Dauer von 1 Jahr postoperativ erneut telefonisch befragt werden. Hierbei wurde die Zufriedenheit und der Rezidivstatus der Patientinnen erfragt und dokumentiert. Wir postulierten, dass sich bezüglich Zufriedenheit und postoperativem Schmerzempfinden zwischen Patientinnen der LA-Gruppe und der AA-Gruppe keine klinisch relevanten signifikanten Unterschiede zeigen würden.In der Machbarkeitsstudie wurden 90% (272 von 303) der Patientinnen mit der Diagnose HSIL oder AIS von Kolposkopiker*innen als geeignet für eine Schlingenexzision in LA angesehen. 75% (227 von 303) der in diesem Rahmen befragten Patientinnen waren offen für eine Operation in LA.In der Vergleichsstudie wurden 63 von 206 Frauen der LA-Gruppe präoperativ befragt: 89% würden bei der Operation einen Schmerzscore über 20 akzeptieren, 33% einen Schmerzscore über 50 und 11% von maximal 20. Postoperativ wurde von 178 Patientinnen für die Schlingenexzision in LA ein mittlerer Schmerzscore von 13,1, für den Injektionsschmerz der LA ein mittlerer Schmerzscore von 20,9 angegeben (p < 0,001). Schmerzen 20 Minuten nach dem Eingriff in LA (n = 178) versus Narkose (n = 80) unterschieden sich nicht signifikant (p = 0,09). Die Operateur*innen beurteilten die Schmerzempfindung der Patientinnen während der Schlingenexzision in LA signifikant geringer als den Schmerz, der von der Patientin empfunden wurde mit einer Unterschätzung von −14,63 Schmerzpunkten auf der VAS (p < 0,001).Die Befragung innerhalb von 7 Tagen nach Schlingenexzision bei 178 Frauen der LA-Gruppe erbrachte, dass 95,5% den Eingriff wieder in LA durchführen ließen (8,8% davon mit zusätzlichen Schmerzmitteln) und 4,5% die Vollnarkose wählen würden. Die telefonische Befragung nach einem mittleren Abstand zur OP von 12 Monaten ergab bei 133 Patientinnen der LA-Gruppe, dass 97% der Patientinnen „zufrieden“ oder „sehr zufrieden“ mit der durchgeführten Behandlung waren. Für Patientinnenzufriedenheit und postoperatives Schmerzempfinden zeigte sich zwischen LA-Gruppe und AA-Gruppe kein signifikanter Unterschied.Für die Rate an Nachblutungen (6,7% vs. 8,1%, p = 0,72), HSIL/AIS Rezidiven (3,6% vs. 5,2%, p = 0,62) sowie der Verteilung des histopathologischen R-Status (R0 89,5% vs. 81,1%, p = 0,73; R1 5,3% vs. 12,2%, p = 0,57, Rx 4,1% vs. 5,4%, p = 0,65) zeigte sich zwischen der LA-Gruppe versus AA-Gruppe kein signifikanter Unterschied.Mehr als 95% der Patientinnen würden wieder die örtliche Betäubung als Anästhesieverfahren wählen, und 97% der Patientinnen zeigten sich auch noch 1 Jahr später zufrieden oder sehr zufrieden mit der Operation in Lokalanästhesie. Das Angebot einer Lokalanästhesie sollte obligat werden und in die entsprechende Leitlinie Aufnahme finden.
Keywords: CIN; Schlingenexzision; Lokalanästhesie